2016
DOI: 10.1159/000450556
|View full text |Cite
|
Sign up to set email alerts
|

Macular Choroidal Thickness in Myopic Eyes with and without a Dome-Shaped Macula: A Case-Control Study

Abstract: Background and Objective: Dome-shaped macula (DSM) has recently been described with myopic staphyloma, which may cause decreased vision. The purpose of this study was to evaluate the choroidal thickness of eyes with and eyes without DSM. Methods: A total of 26 eyes with DSM were paired based on axial length with 26 eyes without DSM. All patients underwent spectral-domain OCT examination using the 7-line EDI (enhanced depth imaging) protocol. The mean choroidal thickness was measured using Early Treatment Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…In another study, they detected decreased choroidal thickness at the periphery but not in the macular area with DSM. 4 Thus, they proposed that DSM might be caused by scleral introversion in resisting the development of staphyloma. 4 Furthermore, Byeon et al suggested that DSM might be associated with posterior staphyloma (PS) (condition which includes extensive protruding of posterior pole plus macular protrusion, extensive protruding of posterior pole plus peripapillary protrusion, and extensive protruding of posterior pole plus inferior staphyloma) or heteromorphosis of the inferior staphyloma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, they detected decreased choroidal thickness at the periphery but not in the macular area with DSM. 4 Thus, they proposed that DSM might be caused by scleral introversion in resisting the development of staphyloma. 4 Furthermore, Byeon et al suggested that DSM might be associated with posterior staphyloma (PS) (condition which includes extensive protruding of posterior pole plus macular protrusion, extensive protruding of posterior pole plus peripapillary protrusion, and extensive protruding of posterior pole plus inferior staphyloma) or heteromorphosis of the inferior staphyloma.…”
mentioning
confidence: 99%
“… 4 Thus, they proposed that DSM might be caused by scleral introversion in resisting the development of staphyloma. 4 Furthermore, Byeon et al suggested that DSM might be associated with posterior staphyloma (PS) (condition which includes extensive protruding of posterior pole plus macular protrusion, extensive protruding of posterior pole plus peripapillary protrusion, and extensive protruding of posterior pole plus inferior staphyloma) or heteromorphosis of the inferior staphyloma. Assuming that the sclera is the thinnest at its peak protrusion area, the macular scleral thickening symptom occurring with complicated staphyloma is a reasonable hypothesis.…”
mentioning
confidence: 99%
“…However, scleral thickening may not be the only physiopathologic mechanism leading to DSM. In the study of Soudier et al [19], choroidal thickness decreases at the periphery but not in the macular area with DSM, suggesting preserved central macular anatomy. Based on this result, Soudier et al suggested that development of DSM may be due to macular anatomical preservation in a growing staphyloma [19].…”
Section: Discussionmentioning
confidence: 85%
“…In the study of Soudier et al [19], choroidal thickness decreases at the periphery but not in the macular area with DSM, suggesting preserved central macular anatomy. Based on this result, Soudier et al suggested that development of DSM may be due to macular anatomical preservation in a growing staphyloma [19]. Soudier et al also showed increase in height of the bulge with time, resulting from perimacular extension of the myopic staphyloma [20].…”
Section: Discussionmentioning
confidence: 85%
“…On two-dimensional images, the macular convexity is better seen in horizontal cross-sectional optical coherence tomography (OCT) scans 1–4. Although the pathogenesis of this unusual tomographic feature remains unclear, possible causes have been suggested in the medical literature, including collapse of the scleral wall attributable to insufficient pressure to keep the ectatic distended,5 tangential vitreoretinal traction,5 resistance to staphylomatous deformation,6 defects on the macular Bruch’s membrane,7 sectional thickness of the sclera within a posterior staphyloma8 9 or the results of a compound staphyloma 10 11…”
Section: Introductionmentioning
confidence: 99%